Bankruptcies, indebtedness and the credit cruch - Kari Takala; Matti Virén (Bank of Finland, 1995)
This paper deals with Finnish bankruptcies.It shows that bankruptcies are strongly related to the business cycle and that they are perhaps even more strongly related to indebtedness, real interest rates and asset prices.The importance of these financial factors probably increased when the financial markets were liberalized in the early 1980s. Although there is a lot of seasonal and cyclical variation in bankruptcies the long run level (especially when adjusted to the number of firms) is almost constant representing some sort of "a natural rate of bankruptcies".What makes bankruptcies so important is the fact that they directly affect production, employment and credit expansion.The credit crunch effect in particular is scrutinized in the paper.
URN:NBN:fi:bof-20140807157
Keywords: 330